International Cooperation among Universities: Accommodating Diversity Within Indian Higher Education - Pranjali Kirloskar; Neeta Inamdar (Ali Khorsandi Taskoh, 2022)
Internationalization of higher education (IHE) has grown in its scope and priority. The history and approach of Indian universities to IHE has been distinct. The recent policy documents such as National Education Policy 2020 and draft document of Science, Technology and Innovation Policy 2020 emphasize on international cooperation of Indian universities. Though there is policy architecture, the response to IHE may differ across universities. This paper argues that, though a few universities have begun to recognize the importance and execution of international engagement, internationalization is not yet uniformly integrated in the Indian HE. The diversity in responses could be due to diversity in terms of number of types of higher education institutions, diversity among study programs, non-uniformities between number of incoming and outgoing students, distinct realities and attitudes towards internationalization among different university structures. We discuss how universities, as actors, are susceptible to change, and thus it is crucial to consider the structural differences among universities while assessing the effectiveness of policies and extent of institutional international engagement. The study may provide insights to higher education leaders and policymakers, who need to weigh different realities to strengthen the global competitiveness of Indian universities.